2011
DOI: 10.1007/s00421-011-2232-5
|View full text |Cite
|
Sign up to set email alerts
|

Does exercise duration affect Fatmax in overweight boys?

Abstract: To compare the assessment of Fat(max) using a single graded exercise test with 3 min stages against 30 min prolonged exercise bouts in overweight boys. Ten overweight boys (8-12 years) attended the laboratory on seven separate occasions. On the first visit, body anthropometrics and peak aerobic capacity ([Formula: see text]O(2peak)) were assessed. Following this, each participant attended the laboratory after an overnight fast for six morning cycling sessions. During the first session, participants completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, while more strict pre-test standardization leads to greater internal validity, it also leads to poorer external validity (i.e harder translation of the results into practice). More generally, while the validity of using a graded exercise tests to determine Fat max has been reported in a number of studies [3], [13], [33], [34], a recent study questions the usefulness using this approach to prescribe training in populations such as highly trained athletes [35]”.…”
Section: Discussionmentioning
confidence: 99%
“…However, while more strict pre-test standardization leads to greater internal validity, it also leads to poorer external validity (i.e harder translation of the results into practice). More generally, while the validity of using a graded exercise tests to determine Fat max has been reported in a number of studies [3], [13], [33], [34], a recent study questions the usefulness using this approach to prescribe training in populations such as highly trained athletes [35]”.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted on lipid oxidation in skeletal muscles during exercise in obese children and/ or adolescents and their findings are contradictory (Crisp et al, 2011;Lazzer et al, 2007;Maffeis et al, 2005;Zunquin et al, 2009). According to our data, lipid oxidation rates did not differ significantly between obese and normal-weight girls at different levels of exercise intensity, despite large differences in adiposity.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, results of studies carried out by Lazzer et al (2007) and Maffeis et al (2005) indicated that lipid oxidation rates did not change significantly between obese and non-obese adolescents at different levels of exercise intensity. Similarly, Crisp et al (2011) reported comparable rates of lipid oxidation in overweight or obese boys compared to normal-weight boys during exercise at 50% _ V O 2max . In contrast, Zunquin et al (2009) found a higher lipid oxidation rate in lean compared to obese boys at moderate exercise intensity only.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Apart that, studies demonstrated how long stage durations are rather time consuming and have an influence on lactate concentrations at the intensity eliciting the FAT max , additionally contributing to correlation assessment bias [3032]. Contrary to LT, using VT demonstrated to be a better index of estimating metabolic thresholds in diverse subjects [2,12,28].…”
Section: Discussionmentioning
confidence: 99%